Modi and the world: (Re) constructing Indian Foreign Policy - Singh, Sinderpal (ed) (New Delhi, 2017)
Contrary to prior expectations, Narendra Modi has expended a significant amount of time, energy and political capital in conducting India's engagement with the outside world since becoming Prime Minister in May 2014. In accordance with wider perceptions about Modi, there were expectations of significant, if not radical, change in Indian foreign policy under his charge. This sentiment led to a section of Indian strategists and foreign policy watchers conceiving the notion of a 'Modi Doctrine' in Indian foreign policy. This notion of foreign policy 'doctrines' is not new to the analysis of Indian foreign policy. Previous incarnations include the 'Indira Doctrine' of the 1970s, the 'Gujral Doctrine' for a brief period in the late 1990s and the 'Manmohan Doctrine' in the period before Modi was elected as prime minister.This edited volume attempts to interrogate the extent to which Indian foreign policy, under Modi, has undergone significant change and the extent to which this manifests itself as a new doctrine in Indian foreign policy. The individual chapters cover key bilateral relationships (the United States, China, Australia and Pakistan) as well as broader regional relationships (South Asia and the Indian Ocean Region) and specific themes (such as economic diplomacy).
Keywords: Politics and government; Diplomatic relations; Narendra Modi